2014
DOI: 10.1155/2014/403703
|View full text |Cite
|
Sign up to set email alerts
|

Brazilin Ameliorates High Glucose-Induced Vascular Inflammation via Inhibiting ROS and CAMs Production in Human Umbilical Vein Endothelial Cells

Abstract: Vascular inflammatory process has been suggested to play a key role in the initiation and progression of atherosclerosis, a major complication of diabetes mellitus. Recent studies have shown that brazilin exhibits antihepatotoxic, antiplatelet, cancer preventive, or anti-inflammatory properties. Thus, we investigated whether brazilin suppresses vascular inflammatory process induced by high glucose (HG) in cultured human umbilical vein endothelial cells (HUVEC). HG induced nitrite production, lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…These major cytokines also mediate the trans-migration of leukocytes to the endothelium leading to endothelial dysfunction and tissue damage. Activation of microvascular endothelial cell by TNF-α and IL-1β lead to increase COX-2 expression and PGE2 production (Turini and DuBois, 2002) while NFκB activation is associated with transcriptional regulation of ICAM-1 and VCAM-1 genes (Jayakumar et al, 2014). In order to determine specific mechanisms that underlie the possible anti-inflammatory effect of BRE, we used our organ specific human primary endothelial cells for modeling the endothelial-leukocyte interaction.…”
Section: Discussionmentioning
confidence: 99%
“…These major cytokines also mediate the trans-migration of leukocytes to the endothelium leading to endothelial dysfunction and tissue damage. Activation of microvascular endothelial cell by TNF-α and IL-1β lead to increase COX-2 expression and PGE2 production (Turini and DuBois, 2002) while NFκB activation is associated with transcriptional regulation of ICAM-1 and VCAM-1 genes (Jayakumar et al, 2014). In order to determine specific mechanisms that underlie the possible anti-inflammatory effect of BRE, we used our organ specific human primary endothelial cells for modeling the endothelial-leukocyte interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of superoxide are elevated and the activities of antioxidant defense substances are reduced in the vessels of diabetic patients and rats, and in endothelial cells exposed to high glucose (HG) (7)(8)(9)(10). Elevated oxidative stress may cause injuries in vascular endothelial cells during the process of diabetic vascular complications (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated oxidative stress may cause injuries in vascular endothelial cells during the process of diabetic vascular complications (11)(12)(13). Excessive reactive oxygen species (ROS) and lipid peroxide initiate and promote endotheliocyte damage (1,7). The antioxidant status of diabetic patients is crucial in preventing oxidative stress and the process of vascular complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a natural product, brazilin has aroused much attention, especially concerning its effect on cardiovascular diseases. Studies focused on the cardiovascular system showed that brazilin inhibits vascular smooth muscle cell proliferation and migration induced by platelet-derived growth factor (PDGF)-BB [17] and ameliorates high glucose-induced vascular inflammation in human umbilical vein endothelial cells [18] . In addition, the effects and some related mechanisms of brazilin in the vascular system have been described.…”
Section: Introductionmentioning
confidence: 99%